The challenges of a randomised placebo-controlled trial of CTO PCI vs. placebo with optimal medical therapy: The ORBITA-CTO pilot study design and protocol - Khan, Sarosh; Fawaz, Samer; Simpson, Rupert; Robertson, Craig; Kelly, Paul; Mohdnazri, Shah; Tang, Kare; Cook, Christopher M.; Gallagher, Sean; O’Kane, Peter; Spratt, James; Brilakis, Emmanouil S.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Percutaneous coronary intervention (PCI) for coronary chronic total occlusion (CTO) has been performed for improvement of symptoms and quality of life for patients with stable angina. The ORBITA study demonstrated the role of the placebo effect in contemporary PCI in non-CTO chronic coronary syndromes however the benefit of CTO PCI beyond that of placebo has not been demonstrated. Aims The ORBITA-CTO pilot study will be a double-blind placebo-controlled study of CTO PCI randomising patients who have 1) been accepted by a CTO operator for PCI 2) symptoms due to a CTO 3) evidence of ischaemia 4) evidence of viability within the CTO territory and 5) a J-CTO score ≤ 3. Methods Patients will undergo medication optimisation that will ensure they are on at least a minimum amount of anti-anginals and complete questionnaires. Patients will record their symptoms on an app daily throughout the study. Patients will undergo randomisation procedure including overnight stay and be discharged the following day. All anti-anginals will be stopped after randomisation and re-initiated on a patient-led basis during the 6-month follow-up period. At follow-up patients will undergo repeat questionnaires and unblinding with a further 2 week unblinded follow-up. Results The co-primary outcomes are of feasibility (blinding) in this cohort and angina symptom score using an ordinal clinical outcome scale for angina. Secondary outcomes include change in quality-of-life measures, SAQ, peak VO2 and anaerobic threshold on cardiopulmonary exercise test. Conclusion The feasibility of a placebo-controlled CTO PCI study will lend to future studies assessing efficacy. The impact of CTO PCI on angina measured using a novel daily symptom app may provide improved fidelity in assessing symptoms in patients with CTO’s.